MÍDIAS SOCIAIS COMO ESTRATÉGIA DE COMUNICAÇÃO EM UMA INSTITUIÇÃO DE ENSINO: PERSPECTIVAS E DESAFIOS - Daniel Augustin Pereira (Universidade Federal de Santa Catarina, 2012)
Professional and technological education, along with the institutions that offer this kind of education, have conquered space in the agenda of Brazilian society. At the same time, people and institutions are paying more attention to new technologies related to communication, especially the social media. In this context, Santa Catarina’s Federal Institute (IF-SC) started adopting, since 2008, social media as a communication strategy with its target audiences: students, staff and the community itself. This case study research aims to analyze the perceptions of IF-SC’s communication professionals as to the institutional use of social media. The results - obtained from interviews, documents and file records - were analyzed using the method of content analysis. The categories of analysis that have emerged are related to the coexistence of social media tools among other communication channels, the benefits and the difficulties that prevent a more effective use of social media in the institution. Among the identified benefits are the rapprochement between the IF-SC and its target audiences, the establishment of a two-way communication channel and the facilitation of access to information about the institution. However, internal organizational difficulties still limit the use of social media as a more effective tool for organizational communication on IF-SC.